Pravo vojnih lica na slobodu vjere u oružanim snagama Bosne i Hercegovine / The right of persons in professional military service to the freedom of faith in the Armed Forces of Bosnia and Herzegovina (Context: Journal of Interdisciplinary Studies, 2022)
This paper analyses the laws and by-laws governing the right of persons in professional military service to the freedom of faith in the Armed Forces of Bosnia and Herzegovina, in conjunction with Article 9 of the European Convention for the Protection of Human Rights and Fundamental Freedoms and BiH legislation, through the following issues: organisation of religious activities and religious service in the BIH Armed Forces, the right to a diet in accordance with religious needs in the BIH Armed Forces, and the right to a leave of absence during religious holidays. The paper particularly analyses the conditions under which there is a possibility for restricting the right to free manifestation of faith, in the part of a by-law restricting the right of persons in professional military service to have a beard, with the exception of religious officers in the BiH Armed Forces. The focus is on the legal obligation of the legislator limiting the right to prove the necessity of such a decision so as to prevent autocracy on the part of the authorities. In addition to a comparative overview of the relevant law and case law, the paper discusses in detail some examples of persons having a beard in the armed forces of several NATO members. Furthermore, the final section of the paper investigates the presence of discrimination, first and foremost through the relationship obtaining with regard to military personnel and religious officers of the same religion and, subsequently, through the issue of equal treatment on the part of the State with regard to prominence of different religious symbols.